1994
DOI: 10.1109/20.305535
|View full text |Cite
|
Sign up to set email alerts
|

The development of texture in Co-Cr films

Abstract: Texture development as a function of film thickness (5-980 nm) was investigated for two series of CoslCr19 films. In general, the films were strongly textured. The orientation ratio, OR,, was used to describe the strength of the texture. Experimental data showed that for the Series A films (5-200 nm), the OR, value increased with increasing film thickness, while for Series B films (46-980 nm), the OR, as a function of the film thickness described a single peak curve, with its maximum near 130 nm. The calculate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

1994
1994
2000
2000

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 18 publications
0
9
0
Order By: Relevance
“…Although the characteristic coercivity of nanowires is mainly determined by their diameters, it has been found that coercivity also depends on the packing density of the alumite template. 6,12 Coercivity of nanowires decreases slightly with increasing packing density, and this can be explained in terms of interwire magnetostatic interactions. 6,12 Previous studies on magnetization reversal of nanowires treated the wires as single-domain infinite cylindrical particles.…”
Section: B Magnetic Reversalmentioning
confidence: 99%
See 2 more Smart Citations
“…Although the characteristic coercivity of nanowires is mainly determined by their diameters, it has been found that coercivity also depends on the packing density of the alumite template. 6,12 Coercivity of nanowires decreases slightly with increasing packing density, and this can be explained in terms of interwire magnetostatic interactions. 6,12 Previous studies on magnetization reversal of nanowires treated the wires as single-domain infinite cylindrical particles.…”
Section: B Magnetic Reversalmentioning
confidence: 99%
“…6,12 Coercivity of nanowires decreases slightly with increasing packing density, and this can be explained in terms of interwire magnetostatic interactions. 6,12 Previous studies on magnetization reversal of nanowires treated the wires as single-domain infinite cylindrical particles. Two reversal modes have been suggested as being important, curling and the coherent rotation mode.…”
Section: B Magnetic Reversalmentioning
confidence: 99%
See 1 more Smart Citation
“…where /3 is the circumferential angle of pole figure. In our case, the value of F(a,/3) is assumed to be equal to F(a), since the texture in the a-Co phase exhibits high degree of rotational symmetry about the film normal [9]. The difference (a 2 -a 1) is equal to 0.1 °.…”
Section: Methodsmentioning
confidence: 99%
“…However, alumite gives good contrast between the iron needles and the aluminium oxide matrix in the SEM and has a very hard surface, which can be used many times for colloid preparations without damaging. A lot of work has been done about the dependence of the magnetic behaviour of alumite on the morphology parameters [17,18]. The magnetic reversal mode in alumite is found to be curling, but the angular dependence of the coercivity suggests particle interactions [19].…”
Section: Magnetic Structures In Fe-alumitementioning
confidence: 99%